2017
DOI: 10.1016/j.bjane.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative surveillance in neurosurgical patients – usefulness of neurological assessment scores and bispectral index

Abstract: Applied together, the assessment of pupils, GCS, Ramsay scale, CNS, Nu-DESC and BIS improved early detection of postoperative neurological complications in PACU after elective craniotomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
8
0
3
Order By: Relevance
“…A total of 4290 studies were screened on the title/abstract. Eventually, 47 studies were assessed full text, of which 27 excluded: delirium diagnosis not reproducible ( n s (number of studies) = 9), [ 20 28 ] full text not found ( n s = 3), [ 29 – 31 ] duplicate ( n s = 3), [ 18 , 32 ] paediatric patients ( n s = 1) [ 33 ], overlapping populations ( n s = 3), [ 4 , 34 , 35 ] no delirium assessment ( n s = 1), [ 36 ] no original data ( n s = 2) [ 37 , 38 ] and an unclear number of patients undergoing intracranial surgery ( n s = 5) [ 39 43 ]. Finally, 20 paper were included in the qualitative analysis and 18 papers in the quantitative analysis ( n p (number of patients) = 5083).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4290 studies were screened on the title/abstract. Eventually, 47 studies were assessed full text, of which 27 excluded: delirium diagnosis not reproducible ( n s (number of studies) = 9), [ 20 28 ] full text not found ( n s = 3), [ 29 – 31 ] duplicate ( n s = 3), [ 18 , 32 ] paediatric patients ( n s = 1) [ 33 ], overlapping populations ( n s = 3), [ 4 , 34 , 35 ] no delirium assessment ( n s = 1), [ 36 ] no original data ( n s = 2) [ 37 , 38 ] and an unclear number of patients undergoing intracranial surgery ( n s = 5) [ 39 43 ]. Finally, 20 paper were included in the qualitative analysis and 18 papers in the quantitative analysis ( n p (number of patients) = 5083).…”
Section: Resultsmentioning
confidence: 99%
“…Um item não levantado a priori, como objetivo do estudo, mas que apresentou destaque no decorrer da pesquisa foi a ausência do carimbo profissional após o registro, foi evidenciado que de 356 registros, 94 (17,5%) não constavam carimbo, apenas o nome por extenso e número do Conselho Regional de Enfermagem (COREN). Estudo evidenciou que a avaliação conjunta do reflexo pupilar e da ECGl são úteis na estimativa de ocorrência de complicações neurológicas no pósoperatório de craniotomias 11 . Embora a evidência supracitada aponte para a necessidade da avaliação concomitante (avaliação do nível de consciência e pupila), o resultado do presente estudo, demonstrou que houve maior quantidade de registros do nível de consciência, que registros de avaliação pupilar.…”
Section: Resultsunclassified
“…(19). Herrero et al (20) compared different methods in the assessment of postoperative neurological complications in neurosurgical patients, and reported that; applied together, the assessment of pupils, Glasgow, Coma Scale, RSS, CNS, The Nursing Delirium Screening Scale (Nu-DESC) and BIS improved early detection of postoperative neurological complications in Post anesthesia care unit (PACU) after elective craniotomies. Yang et al (21) reported that t the number of sedation-related adverse events appears to be lower when BIS was used although the mean level of sedation does not change significantly.…”
Section: Resultsmentioning
confidence: 99%